Expected Price and the Cobweb Theorem - Collery, Arnold P. (Quarterly Journal of Economics, 1955)
Journal Article Expected Price and the Cobweb Theorem Get access Arnold P. Collery Arnold P. Collery Amherst College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 69, Issue 2, May 1955, Pages 315–317, https://doi.org/10.2307/1882157 Published: 01 May 1955